2019
DOI: 10.1093/jncics/pkz026
|View full text |Cite
|
Sign up to set email alerts
|

Circulating Tumor Cells in Early Breast Cancer

Abstract: Circulating tumor cells (CTCs) are particularly rare in non-metastatic breast cancer, and the clinical validity of CTC detection in that clinical setting was initially not well recognized. A cytological CTC detection device (CellSearch) fulfilling the CLIA requirements for analytical validity was subsequently developed and, in 2008, we reported the first study (REMAGUS02) showing that distant metastasis-free survival was shorter in early breast cancer patients with one or more CTCs. In the past 10 years, other… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
57
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
4
1

Relationship

1
8

Authors

Journals

citations
Cited by 80 publications
(60 citation statements)
references
References 64 publications
3
57
0
Order By: Relevance
“…However, we were not able to demonstrate that epithelial CTCs, EMT-CTCs, or CSC-CTCs serve as surrogate markers for pCR. In agreement, ancillary studies of the phase III GeparQuattro and Neo ALTTO trials were not able to confirm an association either; a decrease in the CTC count after neoadjuvant treatment in locally advanced breast cancer was not significantly associated with better response to systemic treatment [27][28][29]. In a more recent meta-analysis of 2090 patients treated with neoadjuvant chemotherapy, CTC detection-before neoadjuvant chemotherapy or before surgery-by CellSearch was also not able to demonstrate a correlation between CTC numbers and pCR [30].…”
Section: Discussionmentioning
confidence: 97%
“…However, we were not able to demonstrate that epithelial CTCs, EMT-CTCs, or CSC-CTCs serve as surrogate markers for pCR. In agreement, ancillary studies of the phase III GeparQuattro and Neo ALTTO trials were not able to confirm an association either; a decrease in the CTC count after neoadjuvant treatment in locally advanced breast cancer was not significantly associated with better response to systemic treatment [27][28][29]. In a more recent meta-analysis of 2090 patients treated with neoadjuvant chemotherapy, CTC detection-before neoadjuvant chemotherapy or before surgery-by CellSearch was also not able to demonstrate a correlation between CTC numbers and pCR [30].…”
Section: Discussionmentioning
confidence: 97%
“…Prognostic significance of CTCs was also clearly demonstrated in adjuvant setting [78]. The randomized trial SUCCESS-A on more than 2000 patients revealed that CTC positivity before as well as after adjuvant chemotherapy was an independent prognostic factor, with poor disease-free survival (DFS) (hazard ratio (HR) = 2.28, 95% CI = 1.48 to 3.50) and OS (HR = 3.95, 95% CI = 2.13 to 7.32).…”
Section: Early Breast Cancer; Prognostic Value Programs and Trialsmentioning
confidence: 92%
“…The small number of CTCs per ml of peripheral blood is the major challenging physical limit. CTCs are particularly rare in non-metastatic breast cancer, usually less than 1 CTC/10 mL of blood is found [78], with five or more CTCs being a rare event (1-5.9%) [79]. CTCs are detectable in about 20% to 25% of patients with localized nonmetastatic breast cancer at the time of diagnosis using a lower threshold (≥1 CTC per 7.5 mL blood) than in MBC (≥ 5 CTC per 7.5 mL blood) [79][80][81][82].…”
Section: Early Breast Cancer; Prognostic Value Programs and Trialsmentioning
confidence: 99%
“…Our results demonstrated that CTCs were present even in stage 0 or I melanoma. Although CTCs are present in limited numbers [9], they exist even in the early stages of melanoma, as well as in other diseases such as breast and lung cancer [18][19][20] Primary tumors with minimal invasion may exert their metastatic potential via releasing CTCs.…”
Section: Discussionmentioning
confidence: 99%